Leadership of the Golkar Party after the New Order (Comparative Study of Leadership Patterns of Akbar Tandjung [Period 1999-2004] and Muhammad Jusuf Kalla [Period 2004-2009] in the Golkar Party) - Nurcholifah Nurcholifah (Trigin Publisher, 2022)
In this study, the author focuses on the discussion on the leadership of the former chairman of the Golkar Party, Akbar Tandjung, who was the general chairman of the Golkar Party for the 1999-2004 period and Muhammad Jusuf Kalla, who was the general chairman of the Golkar Party for the 2004-2009 period. This the author does so that the discussion becomes the focus and does not expand to a longer period due to the limitations of the author. This study uses a qualitative approach, using the results of interviews as the primary source. The secondary sources were obtained from various literatures, both from books, magazines, and articles on the internet. Interviews were conducted with the two figures, namely Akbar Tandjung and Jusuf Kalla using an interview guide (interview guide). This is done by the author so that the interview does not expand to things outside the discussion and becomes a focus on the core problems that want to be analyzed in this thesis. Based on the results of the research and analysis that the authors have done, it can be concluded that Akbar Tandjung's leadership style is more paternalistic. This can be seen from how Akbar Tandjung made decisions regarding the policies of the Golkar Party which prioritized harmony among fellow administrators by involving many seniors to get direction. Meanwhile, Jusuf Kalla's leadership style is democratic. Jusuf Kalla's background as an entrepreneur is not surprising if the policies taken by Jusuf Kalla are efficient, straightforward, and straightforward.